The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2002
DOI: 10.1055/s-2002-35344
|View full text |Cite
|
Sign up to set email alerts
|

Magnetresonanztomographie (MRT) des Kiefergelenkes: Einfluss auf Therapieentscheidung und Übereinstimmung zweier Auswerter

Abstract: MRI has a measurable impact on the therapeutic approach to the internal derangement of the TMJ. The position of the disk and condyle can be reproducibly judged, while the signal intensity of the disk and bilaminar zone and the osseous changes are subject to wide observer variations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
1
0
4

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 9 publications
1
1
0
4
Order By: Relevance
“…The highest interobserver agreement among the seven observers was found for the variable combination "disk position at closed-mouth position and at maximum opening in the sagittal plane." The kappa value, however, was lower than the values found in studies by Nebbe et al, 7 Tasaki et al, 6 and Orsini et al, 10,11 but similar to the value found in the study by Vahlensieck et al 20 As in the study by Nebbe et al, 7 the greatest agreement was found for the category "anterior disk position without reduction." Nebbe et al 7 found very good agreement and we found good agreement among observers for this category.…”
Section: Discussionsupporting
confidence: 64%
“…The highest interobserver agreement among the seven observers was found for the variable combination "disk position at closed-mouth position and at maximum opening in the sagittal plane." The kappa value, however, was lower than the values found in studies by Nebbe et al, 7 Tasaki et al, 6 and Orsini et al, 10,11 but similar to the value found in the study by Vahlensieck et al 20 As in the study by Nebbe et al, 7 the greatest agreement was found for the category "anterior disk position without reduction." Nebbe et al 7 found very good agreement and we found good agreement among observers for this category.…”
Section: Discussionsupporting
confidence: 64%
“…In the axially corrected coronal plane, the disc is not centred between the condyle and eminence in either the medial or the lateral parts Disc not visible: Neither signal intensity nor outline make it possible to define a structure as the disc Several studies of observer agreement at MRI of the TMJ have been published. [10][11][12][13][14][15][16][17] It is difficult to compare the studies as different criteria were used, for instance for disc position. Widmalm et al 16 concluded that a diagnosis of TMD based on MRI examination protocols made by a single examiner should not be accepted, as the diagnosis may be misleading.…”
Section: Discussionmentioning
confidence: 99%
“…Dabei kann es zum direkten Kontakt der beiden Knochen und zu einer Perforation der bilaminären Zone kommen [6]. [29]. Beim Vergleich der klinischen Befundung mit MRT-Aufnahmen zeigt sich eine schlechte Überein-stimmung, die in der Regel auf falsch negativen klinischen Befunden beruht.…”
Section: Alterunclassified
“…Dabei ist die Untersucherabhängigkeit der Kiefergelenk-MRT bei den verschiedenen Strukturen sehr unterschiedlich. So wurden gute Übereinstimmungen zwischen verschiedenen Untersuchern bei Parametern wie der Diskus-und Condylusposition beschrieben, während die Konkordanz bei Parametern wie der Signalintensität des Diskus und der bilaminä-ren Zone deutlich schlechter war [29]. Die genaue Klassifikation von Kiefergelenkveränderungen ist aber von hoher klinischer Relevanz, da ein breites Spektrum an konservativen (verschiedene Schienen, Physiotherapie, medikamentös) und operativen (vor allem in den Benelux-Staaten, Japan und den USA) Therapiemög-lichkeiten besteht [33 -35].…”
Section: Alterunclassified